Clinical Features, Treatment, and Outcome of Macrophage Activation Syndrome Complicating Systemic Juvenile Idiopathic Arthritis: A Multinational, Multicenter Study of 362 Patients. Issue 11 (November 2014) - Minoia, Francesca; Davì, Sergio; Horne, AnnaCarin; Demirkaya, Erkan; Bovis, Francesca; Li, Caifeng; Lehmberg, Kai; Weitzman, Sheila; Insalaco, Antonella; Wouters, Carine; Shenoi, Susan; Espada, Graciela; et al.
<x xml:space="preserve">Abstract</x> Objective To describe the clinical, laboratory, and histopathologic features, current treatment, and outcome of patients with macrophage activation syndrome (MAS) complicating systemic juvenile idiopathic arthritis (JIA). Methods In this multinational, multicenter study, pediatric rheumatologists and hemato‐oncologists entered patient data collected retrospectively into a web‐based database. Results A total of 362 patients, 22% of whom had MAS at the onset of systemic JIA, were included in the study by 95 investigators from 33 countries. The most frequent clinical manifestations were fever (96%), hepatomegaly (70%), and splenomegaly (58%). Central nervous system dysfunction and hemorrhages were recorded in 35% and 20% of the patients, respectively. Platelet count and liver transaminase, ferritin, lactate dehydrogenase, triglyceride, and d‐dimer levels were the sole laboratory biomarkers showing a percentage change of >50% between the pre‐MAS visit and MAS onset. Evidence of macrophage hemophagocytosis was found in 60% of the patients who underwent bone marrow aspiration. MAS occurred most frequently in the setting of active underlying disease, in the absence of a specific trigger. Nearly all patients were given corticosteroids, and 61% received cyclosporine. Biologic medications and etoposide were given to 15% and 12% of the patients, respectively. Approximately one‐third of the patients required admission to the intensive care unit (ICU), and the mortality rate was 8%. Conclusion This study provides information on the clinical spectrum and current management of systemic JIA–associated MAS through the analysis of a very large patient sample. MAS remains a serious condition, as a sizeable proportion of patients required admission to the ICU or died.